Power: An Example of Its Changing Nature - Rees, Ruth (Canadian Journal of Higher Education, 1999)
The purpose of the paper is to describe some experiences of a female Associate Dean in a university faculty in terms of the Marshall (1984) typology of power to reveal its changing nature — evolving from a traditional perspective of having power over others towards one of a "web of relations" (Burbules, 1986). The typology, broadened through the literature review, contains five components of power: power over others, a traditional perspective; structural factors; power through others or facilitative power; power with others or empowerment; and personal power. The experiences of the author reveal that she sees herself as having little power over others and having many aspects of personal power. This finding is similar to two previous studies with women as managers (Adler, Laney, & Packer, 1993; Millers & Cummins, 1992). However, the author self-reflects that most of her power is facilitative power, although she believes that the ideal form we should strive for in the university would be empowerment, where the leader is the web builder so that others can be creating and generating power.